Romantic Beliefs in Dating Life: Its Impact on Satisfaction in Emerging Adults - Pricilia, Bella; Theresia, Allessandra (Jurnal Psikologi Terapan, 2023)
This study aims to determine the influence of *romantic beliefs* on relationship satisfaction in individuals within the phase of emerging adulthood. This phase is marked by significant changes in individual development, including romantic relationships. The method used in this research is simple regression analysis, with data collection through questionnaires completed by eligible respondents. The results show that *romantic beliefs* have a significant impact on relationship satisfaction, where higher romantic beliefs are associated with lower levels of relationship satisfaction. These findings contradict the initial hypothesis, which suggested that *romantic beliefs* would enhance relationship satisfaction. Based on these results, the study suggests that individuals should adopt more realistic views on romance in order to maintain the quality of their relationships. Additionally, the implications of this research can contribute to the development of interpersonal relationship theories, particularly in the context of emerging adulthood, and serve as a consideration for counselors or psychological practitioners in providing guidance on romantic relationships